Louvre Le Collège de France et le musée du Louvre - Desclaux, Jessica (Passage des disciplines, 2020)
The fourth volume of the "Passage des disciplines" collection looks at how the discipline of art history was established at the Collège de France by forging a special link with the Musée du Louvre. Georges Lafenestre, André Michel, Paul Vitry, and René Huyghe were curators in the Department of Paintings and Drawings and the Department of Medieval, Renaissance and Modern Sculptures, before holding the Chair of Aesthetics and Art History, created in 1878 and once renamed "History of French Art" (1920-1925), or the municipal chair, "Psychology of Visual Arts" (1951-1976), financed by the City of Paris. By electing several curators to its chairs in this way, does the Collège de France single itself out among the institutions at which aesthetics and art history are taught? What determines the recruitment of curators? To what extent does their museum experience weigh on their appointment? Once elected, what ties do they maintain with the Louvre? Do they integrate the museum's debates on aesthetics or historical method into their teaching at the Collège de France? Such are some of the questions that the authors of this volume explore, drawing on the archives of various institutions. This volume ensues from a study day organised by Jessica Desclaux (Sorbonne Université-Musée du Louvre/Centre Dominique-Vivant Denon) on 4 April 2019, as part of the research programme "Passage des disciplines: global history of the Collège de France, 19th-20th century". The programme focuses on the selection process of chairs and fields of study at the Collège de France, including those that were not admitted to it and which formed a "virtual college", from the late 18th century to the 1960s. It is directed by Antoine Compagnon, with the collaboration of Céline Surprenant, and has received financial support from PSL (2016-2019) and the République des Savoirs.